2010
DOI: 10.1016/j.ijantimicag.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Daily serum piperacillin monitoring is advisable in critically ill patients

Abstract: The aim of the present study was to evaluate the benefit of monitoring serum piperacillin concentrations in critically ill patients. This was an 11-month, prospective, observational study in a 30-bed Intensive Care Unit in a teaching hospital, involving 24 critically ill patients with evidence of bacterial sepsis. All patients received a 66 mg/kg intravenous bolus of piperacillin in combination with tazobactam (ratio 1:0.125) followed by continuous infusion of 200 mg/kg/24 h. The dosage was adjusted when the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 14 publications
2
35
0
1
Order By: Relevance
“…No patients received an increased dosage. Dr. Blondiaux and colleagues reported that TDMguided dose adjustment was required in 50% of patients for the continuous infusion of PIPC in combination with tazobactam [23]. Similarly, in this study, the patients required a correction of their initial regimens following TDM and the most of them were successful in decrease beta-lactam dosages in the present study.…”
Section: Dose Individualizationsupporting
confidence: 66%
“…No patients received an increased dosage. Dr. Blondiaux and colleagues reported that TDMguided dose adjustment was required in 50% of patients for the continuous infusion of PIPC in combination with tazobactam [23]. Similarly, in this study, the patients required a correction of their initial regimens following TDM and the most of them were successful in decrease beta-lactam dosages in the present study.…”
Section: Dose Individualizationsupporting
confidence: 66%
“…Recent retrospective studies support this optimized dosing in critically-ill patients, 26,27 with relevant data available for piperacillin-tazobactam, ceftazidime, cefepime and meropenem. 23 The choice of continuous versus extended infusion of beta-lactams should be guided by the stability of the drug at room temperature.…”
Section: This Issue Of Haematologica 21mentioning
confidence: 79%
“…has not yet been a standard practice across the world, studies have demonstrated the clinical utility of this methodology in critically ill patients [12,[36][37][38][39][40]. The level of evidence supporting TDM program for these antibiotics is strong with increasing interest in further demonstrating its impact on clinical outcomes [41].…”
Section: Page 8 Of 48mentioning
confidence: 99%